Factors associated with psoriasis in a French Nationwide HIV cohort: the independent role of HLA-B*57:01. (1st June 2020) - Hentzien, Maxime; Cuzin, Lise; Raffi, François; Jacomet, Christine; Reynes, Jacques; Rey, David; Ravaux, Isabelle; Cheret, Antoine; Viguier, Manuelle; Bani-Sadr, Firouzé
Abstract : Objective: Psoriasis is a T-cell-mediated inflammatory disease with genetic factors involved in its etiopathogenesis. In non-HIV populations, HLA-B * 57:01 has been associated with a higher risk of psoriasis. The aim of this study was to investigate demographic and immunovirological characteristics associated with psoriasis, and to assess whether HLA-B * 57:01 is associated with psoriasis among people living with HIV (PLHIV) followed in a large French multicenter Dat'AIDS cohort. Methods: All PLHIV followed up from January 2000 to December 2018 with an available result for HLA-B * 57:01 were included. Logistic regression models were used to identify associations between psoriasis (outcome variable) and explanatory variables. Results: Among 31 076 PLHIV, the overall prevalence of psoriasis and HLA-B * 57:01 were 2.25 and 4.73%, respectively and varied according to ethnicity. By multivariate analysis, male gender [OR 1.81 (95% CI 1.46–2.24), P < 10 –4 ], positive HLA-B * 57:01 [OR 2.66 (95% CI 2.12–3.33), P < 10 –4 ], nadir CD4 + cell count less than 200 cells/μl [OR 1.41 (95% CI 1.19–1.67), P < 10 –4 ] and positive HCV serology [OR 1.45 (95% CI 1.20–1.76), P < 10 –4 ] were significantly associated with a higher risk of psoriasis. Being born in West and Central Africa [OR 0.15 (95% CI 0.10–0.25), P < 10 –4 ], the Caribbean islands [OR 0.14 (95% CI 0.05–0.45), P = 0.0008] or Latin America [OR 0.31 (95% CI 0.14–0.69), P = 0.004] was associated with a lower risk of psoriasis compared with patients born in mainland France. Conclusion: PLHIV carrying HLA-B * 57:01 have around a three-fold increased risk of psoriasis. This association might provide a possible explanation for the observed differences in psoriasis prevalence between ethnic groups.